Spatio-temporal Dynamics of Carbachol-induced Rhythmic Neural Activities in the Hippocampus in vitro - KATAYAMA, Norihiro; WATANABE, Naoki; KIKUCHI, Osamu; NAKAO, Mitsuyuki; KARASHIMA, Akihiro (Transactions of Japanese Society for Medical and Biological Engineering, 2004)
Oscillatory neural activities, such as theta rhythm (4-12Hz) and high-frequency burst waves (>100Hz) in the hippocampus, are expected to play an important role in the learning and memory functions of the brain. Neural oscillations are also observed in a hippocampal slice preparation in the presence of carbachoL Therefore, this preparation has been used as an in vitro model for studying the rhythms. In this study, local field potentials and multi-neuron activities were simultaneously recorded at two sites that are 0.4mm apart from each other in the pyramidal cell layer of the CA3b area in the slices because the rhythmic activities are often initiated in this area. This study was carried out in order to study the manner in which the rhythmic activities initiate and spread in the area. It was shown that the generation and disappearance of the theta, beta (12-25Hz), and gamma (25-80Hz) rhythms were spatially coherent. Neural spike timings of CA3 neurons tended to lock to a particular phase of the field potential oscillations. In contrast, in the case of high-frequency burst waves, the phase gap between the recording sites changed with the passage of time. These results suggest that the generation and synchronization mechanism of high-frequency burst waves are completely different from those of the other rhythmic waves: the theta, beta, and gamma waves.